LEGAL AND EXTRA-LEGAL MECHANISMS OF INTERNET CENSORSHIP IN KAZAKHSTAN. - Rakhmetov, Baurzhan (Asian Affairs, 2026)
This article examines internet censorship in Kazakhstan, focusing on the interplay between legal frameworks and extra-legal mechanisms. Drawing on 17 semi-structured interviews with journalists, media experts, and digital rights specialists, thematic analysis, and an analysis of relevant digital legislation, the study demonstrates how the Kazakhstani state systematically combines broad and ambiguously defined laws with prosecution, intimidation, harassment, and co-optation to control online expression. The findings illustrate that while formal regulations provide legitimacy and structure for censorship, informal coercion is crucial for enforcing compliance and fostering self-censorship among journalists, activists, and internet users. By integrating legal and extra-legal methods, Kazakhstan exemplifies a hybrid model of digital authoritarianism, in which control over the internet is achieved not only through regulation but also by shaping the motivations and fears of digital actors. The article contributes to broader debates on digital authoritarianism and authoritarian resilience.